BMI and sociodemographic characteristic among patients with tuberculosis attending a DOTS clinic at a tertiary care hospital in Kathmandu, Nepal - Shrestha, Supri Raj; Shrestha, Niraj; Dhakal, Nishchal (Nepal Medical College Journal, 2023)
Tuberculosis (TB), an infectious disease caused by Mycobacterium tuberculosis is a serious public health threat in low- and middle-income countries. In tuberculosis, the sociodemographic aspects play a significant role in increasing the susceptibility to infection. The current study aimed to study the BMI and sociodemographic characteristic among patients with tuberculosis attending a DOTS clinic at a tertiary care hospital of Kathmandu. An observational descriptive cross sectional study using census sampling technique was conducted among 170 persons with tuberculosis coming for ATT drugs in Community Medicine OPD of Nepal Medical College Teaching Hospital. The information was obtained using self-constructed structured questionnaire from the study population. The information regarding socioeconomic characteristics, medical and family history, type and clinical presentation of tuberculosis and anthropometric measurement were taken. Out of 170 tuberculosis patient 93 had pulmonary tuberculosis, 71 had extrapulmonary tuberculosis and 6 had both. The different types of tuberculosis showed the association with occupation of respondents, family types, socioeconomic status, family size, BCG scar and social habits before tuberculosis. Weight loss and cough were most common clinical presentation among the participants whereas lymphnode and gastrointestinal tract were most common sites for extrapulmonary tuberculosis. According to BMI, 16.5% of the study population were underweight. Thus, the present study provides valuable information regarding association of sociodemographic factors with tuberculosis and nutritional status of persons with tuberculosis.